Google sala de aula na formação inicial de professores: caminhos e desafios da educação 4.0 - Martins, Izabel Cristina Vieira (2022)
The XXI century educational context requires teachers to follow the development of the contemporary society, in which they need to keep up with the latest technologies to explore its pedagogical potential, as well as to create different and exciting learning situations. The present research was developed in the area of Educational Technologies in Network for Innovation and Democratization of Education, in the research line Management of Educational Technologies in Network and has the following research problem: to what extent will the workshops offer in training, mediated by Google Classroom, contribute to developing technological-pedagogical fluency for the initial teacher training in the Normal Course? We listed as our main objective to analyze the changes produced by the intervention of the initial teacher training, mediated by Google Classroom, for the development of technological-pedagogical fluency, enabling learning situations to be applied in teaching practice. To do that, we developed technologicalpedagogical training workshops mediated by the Google Classroom virtual environment. This study adopted an exploratory qualitative investigation, which is based on the deductive method and the assumptions of action research. Regarding the data collection instruments used in this study, it was adopted questionnaires, field diaries, interviews, and observations of the productions carried out during the training course. The qualitative analysis was built in the construction of four categories, based on the content analysis method according to Bardin (2016). The results indicate that the training workshops enabled future teachers to tread paths toward Education 4.0, creating conditions to enhance technical, pedagogical, and emancipatory knowledge, developing technological-pedagogical fluency. The research resulted in two products, a technical report that presents the Study Unit developed to carry out training workshops and pedagogical and technological guidelines for training teachers in line with education 4.0.